2018
DOI: 10.1111/jvh.13035
|View full text |Cite
|
Sign up to set email alerts
|

High response and re‐infection rates among people who inject drugs treated for hepatitis C in a community needle and syringe programme

Abstract: Summary To achieve WHO hepatitis C virus (HCV) elimination targets by 2030, mathematical models suggest there needs to be significant scale‐up of treatment among people who inject drugs (PWID). We tested whether people who actively inject drugs can be recruited and treated successfully through a community needle and syringe programme (NSP), and assessed rates of re‐infection. 105 HCV RNA positive participants were enrolled prospectively. Participants were recruited from the largest NSP in Dundee over 42 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
37
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 41 publications
(110 reference statements)
2
37
1
2
Order By: Relevance
“…Compliance to treatment was excellent and no minor or serious adverse events were reported. Moreover, no re‐infections were recorded at the last visit, unlike previous studies, in which reinfection were reported . This discrepancy might reflect the fact that most of our population was undergoing substitution therapy, whereas the previous studies were conducted in patients enrolled in community and needle syringe programmes in which most subjects are active substance users and are therefore at a higher risk of reinfection than our patients .…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Compliance to treatment was excellent and no minor or serious adverse events were reported. Moreover, no re‐infections were recorded at the last visit, unlike previous studies, in which reinfection were reported . This discrepancy might reflect the fact that most of our population was undergoing substitution therapy, whereas the previous studies were conducted in patients enrolled in community and needle syringe programmes in which most subjects are active substance users and are therefore at a higher risk of reinfection than our patients .…”
Section: Discussioncontrasting
confidence: 61%
“…This discrepancy might reflect the fact that most of our population was undergoing substitution therapy, whereas the previous studies were conducted in patients enrolled in community and needle syringe programmes in which most subjects are active substance users and are therefore at a higher risk of reinfection than our patients . Also the shorter follow‐up period (6 months) in our study versus 18 months and beyond in other studies could also explain this discrepancy . However, there is now extensive evidence that PWUD affected by HCV can be successfully targeted and treated …”
Section: Discussionmentioning
confidence: 66%
“…In general, the risk of HCV reinfection should be estimated regarding the specific characteristics of the population studied, but should not withhold treatment providers from treating individuals. In a Scottish NSP with very recent PWID, the HCV reinfection incidence rate was indeed 21.5 per 100 py, and even 34.6 in active PWID below the age of 30 years . Although the incidence rates found by Latham et al are low, it is likely that high reinfection rates will be found, if larger PWID populations are treated.…”
mentioning
confidence: 84%
“…On this background, the Scottish study by Schulkind and colleagues is pivotal public health research. 3 First, it provides HCV treatment outcomes and post-treatment reinfection rates in a truly "current" or "active" PWID population. The enrolment criteria of an episode of injecting drug use within the previous week and the median number of injections within the previous week of 6.5 clearly characterize the study population as high-risk.…”
mentioning
confidence: 99%
“…Most studies of current PWID have defined recency of injecting as in the previous six, or even 12 months. 3 Second, the study setting is a needle syringe program (NSP) site, a crucial point of engagement for PWID in relation to HCV prevention, and more recently HCV testing and linkage to care.…”
mentioning
confidence: 99%